2010
DOI: 10.1158/1078-0432.ccr-09-3318
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Analysis and Phase 1 Study of MRX-1024 in Patients Treated with Radiation Therapy with or without Cisplatinum for Head and Neck Cancer

Abstract: Purpose: A previous study reported radiation protection from mucosal injury with D-methionine (D-met) in preclinical evaluation; therefore, the pharmacokinetics, safety, and utility of D-met were evaluated clinically.Experimental Design: The pharmacokinetics of D-met following oral administration of a bioavailable formulation (MRX-1024) was evaluated in normal volunteers. Subsequently, 25 patients were enrolled on a phase 1 study of MRX-1024 concurrent with radiation therapy (RT) with or without weekly cisplat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 40 publications
(75 reference statements)
2
14
1
Order By: Relevance
“…Several animal studies have shown that D-Met prevented oxidative-stress induced ototoxicity and nephrotoxicity from cisplatin treatment (Campbell et al, 1996;Reser et al, 1999). Hamstra et al (2010) evaluated the safety of the MRX-1024 -the bioavailable suspension of D-Met -in cancer patients. They showed that MRX-1024 decreased the rate and severity of oral mucositis, with no significant increase in toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Several animal studies have shown that D-Met prevented oxidative-stress induced ototoxicity and nephrotoxicity from cisplatin treatment (Campbell et al, 1996;Reser et al, 1999). Hamstra et al (2010) evaluated the safety of the MRX-1024 -the bioavailable suspension of D-Met -in cancer patients. They showed that MRX-1024 decreased the rate and severity of oral mucositis, with no significant increase in toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…The long clinical use of D‐met plus the preclinical data showing protection from mucosal injury led to a previously reported phase I clinical trial in which 25 patients with SCCHN were treated with fractioned RT (with 78% also receiving cisplatin) . Pharmacokinetic analysis revealed that when administered orally at 100 mg/kg, peak and area under the curve (AUC) levels of D‐met were comparable to the levels previously associated with mucosal protection in rodents.…”
Section: Introductionmentioning
confidence: 81%
“…D-met reportedly provides selective protection for non-transformed, versus transformed, cells (7), in keeping with our observation that it does not affect tumor growth ± radiation. The use of D-met in human studies resulted in mild-moderate side effects, but it appeared beneficial for limiting the occurrence of severe oral mucositis (8). Racemic mixtures of D- and L-met have long been used for acetaminophen-induced hepatotoxicity (e.g., 21).…”
Section: Discussionmentioning
confidence: 99%